Socio-economic status of the recipients of social security allowance: a case study of Kaski, Nepal - Ranabhat, Deepesh; Adhikari, Sujita; Sapkota, Pradeep; Ranabhat, Mala (Nepalese Journal of Insurance and Social Security, 2021)
The research aims to assess the impact of social security allowance on socio-economic status of the recipients and differences in socio-economic status of the recipients. Multistage sampling technique has been used for the selection of samples. The data has been collected through self-structured questionnaires from 170 respondents who have been receiving social security allowance provided by the Government of Nepal. Thus, descriptive as well as cross-sectional research design has been used for this study. The study found that social security benefits play very important role in improving socio-economic status of the beneficiaries by enhancing the economic well-being, health access, social status, self-respect and respect from others, and living standard of the recipients. The study also found that there is a significant difference in socio-economic well-being of recipients by area of residence, employment status, duration of getting allowance, and allowance as major source of income.